PENERAPAN INTERVENSI TERAPI LATIHAN PEMBEBANAN BERTAHAP TERHADAP KEMAMPUAN MOBILITAS FISIK PADA PASIEN PASCA BEDAH ARHTROTOMY: STUDI KASUS - Syafa Azzahra; Urip Rahayu; Titis Kurniawan (SINERGI : Jurnal Riset Ilmiah, 2026)
Septic arthritis is a musculoskeletal infection that can lead to permanent joint damage if not managed promptly and adequately. Patients following arthrotomy commonly experience pain and decreased muscle strength due to immobilization, which contributes to impaired physical mobility. Gradual weight-bearing exercise is a rehabilitative intervention aimed at improving muscle strength, reducing pain, and enhancing ambulatory ability. This study employed a descriptive case study design involving a 47-year-old male patient diagnosed with post-arthrotomy of the right knee due to septic arthritis at RSUD Umar Wirahadikusumah in March 2025. The intervention was administered over four consecutive days with progressive loading adjusted to the patient’s tolerance. Evaluation was conducted using Manual Muscle Testing (MMT), Numeric Rating Scale (NRS), and Functional Ambulation Category (FAC). The results demonstrated an improvement in physical mobility, indicated by decreased pain levels, increased muscle strength, and gradual enhancement in ambulatory function. Therefore, gradual weight-bearing exercise is considered an effective nursing intervention in supporting the recovery of musculoskeletal function in post-arthrotomy patients with septic arthritis